Treatment of subacute osteoporotic vertebral compression fractures with percutaneous vertebroplasty – A case report - Aleksić, Zoran; Stanković, Ivana; Živanović-Mačužić, Ivana; Jeremić, Dejan; Radunović, Aleksandar; Milenković, Zoran; Stojković, Andjelka; Simović, Aleksandra; Stojadinović, Ivan; Vulović, Maja (Vojnosanitetski pregled, 2020)
Abstract Introduction. Percutaneous vertebroplasty (PVP), as a mini-invasive approach in the treatment of patients with osteoporotic vertebral compression fractures (OVCFs), provides stabilization of the spine and relives pain. The most commonly it is applied in the 3–6 weeks before bending of the spine. Complete cessation of pain is easier to achieve if you treat “less mature” fractures. The aim of the report is to show that PVP is effective and safe for old fractures too. Case report. A 77-old patient suffered from a stable compression fracture of 3th lumbar (L3) vertebral body after minor trauma. This fracture was clinically and radiologically diagnosed. The conservative treatment that included lumbo-sacral orthosis (LSO), analgesic drugs and physical therapy, was primarily applied due to permanent pain and type of fracture. After a period of two months, pain persisted, but it was localized in a thoracic spinal segment with radiologically diagnosed fractured bodies of 8th (Th8) and 10th (Th10), thoracic vertebra without neurological deficit. Thoraco-lumbo-sacral orthosis (TLSO) was prescribed and after six months the indication for vertebroplasty of the Th8 and Th10 vertebral body was given. The pain relief had been achieved and the patient was discharged from the Clinic for Orthopedics on the postoperative day 2, and was symptom free during the follow-up period. Conclusion. In patients with stable OVCFs, PVP is an effective therapy for reducing pain and improving mobility of 6 months old fractures.